Women Leaders Bring Indigenous and Black Issues to Colombia Peace Table. Issue 1 (June 2016) - Bailey, Kay
Labour leader Agripina Hurtado Caicedo, land rights leader Francia Elena Márquez Mina and international advocate Gimena Sánchez-Garzoli are three extraordinary women working to bring peace to Afro-Colombian communities after five decades of violent conflict and centuries of discrimination and disempowerment. Agripina grew up among sugar cane cutters, whose working conditions 20 years ago deteriorated to such an extent that they came to resemble modern-day slavery. As a union leader, she fought to have the protections of Colombia's labour laws implemented and she has also endured violent antiunion harassment, including the murder of her daughter and unborn grandchild. Agripina is currently president of the Afro-Colombian Labour Council and works on behalf of Afro-Colombian workers to end discrimination and unfair labour practices. Francia comes from one of many communities whose lands and livelihoods have been threatened by big mining companies. The corporations' industrial approach devastates the ecosystem and displaces thousands of Afro-Colombians to urban violence and lives of destitution. In 2010, Francia led her community to victory through peaceful protests and court battles against the holder of an illegal mining permit. Since then, she, as a member of Black Communities Process, has been advocating at the national and international levels against environmental destruction and the displacement. Gimena is based in Washington but, with close ties to Afro-Colombian activists, she has become the go-to person for trade unions, displaced Afro-Colombian communities and human rights networks when they need protection and international support.